Pasang Surut dan Arus di Muara Sungai Kapuas Sepok Pangkalan, Teluk Bengkolan Berdasarkan, Kalimantan Barat: Pasang Surut dan Arus di Muara Sungai Kapuas Sepok Pangkalan, Teluk Bengkolan Berdasarkan, Kalimantan Barat - Kushadiwijayanto, Arie Antasari; Nurrahman, Yusuf Arief; Sofiana, Mega Sari Juane; Safitri, Ikha (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
Tides and currents influence the dynamics and biochemical circulation in a bay or estuary. This research aims to conduct an initial study of tides and currents in Bengkolan Bay, which is home to the mangrove ecosystem in West Kalimantan Province. Elevation and current measurements were carried out for 15 days at the mouth of the Kapuas River Sepok Pangkalan (north side of Bengkolan Bay) using tidal palms and drifters. The measurement results show that the pattern of water surface movement and currents at the research location is very dependent on ocean tidal patterns. Diurnal tides play a very large role (10 times) compared to semidiurnal tides. This big role causes the type of tides in Bengkolan Bay to be diurnal. Although semidiurnal tides have a small contribution, shallow water tidal constituent are actually caused by semidiurnal tidal energy dissipation.